Analisis Video Reels Terhadap Pemasaran Digital Untuk Meningkatkan Engagement Media Sosial Instagram @ruasjaricoffee - Iqbal, Muhamad; Sembiring, Evaliata Br (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2024)
Cafe Ruas Jari has recently experienced a decline in visitors, so the management needs innovative promotional media. Adapting to current trend developments, the management of Cafe Ruas Jari highlights promotional activities through social media. This is because social media has the opportunity to increase the number of visitors who come to Cafe Ruas Jari. This research focuses on creating promotional content in the form of videos that will be distributed via social media, then analyzing the increase in visitors through Instagram engagement. The research method used is Research and Development, namely creating promotional content in the form of video reels, which is then analyzed in order to determine the development of video promotional content based on the AIDA approach model. This analysis is carried out by measuring aspects of the development of engagement and insight contained in promotional video content that has been published on Instagram. The research results show that promotional content that has interaction and is produced using the AIDA model has quite a significant difference in user reach when compared to previous videos. There has been an increase in engagement on the Finger Segment Instagram to increase visitors and through respondents' assessment that the video meets the criteria for use as promotional media and can attract the attention of the audience.